1997
DOI: 10.5271/sjweh.192
|View full text |Cite
|
Sign up to set email alerts
|

Asthma in patients with farmer's lung during a five-year follow-up

Abstract: Objectives This study assessed the incidence of asthma in patients with farmer's lung. Methods The study population consisted of 103 1 patients who had occupational fanner's lung diagnosed from 1983 to 1988. The cases of farmer's lung were registered in the nationwide Register of Occupational Diseases by the Finnish Institute of Occupational Health, and all the patients in the study had received compensation from the insurance company for an occupational disease. The diagnosis of asthma was based on entitlemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…Nonspecific bronchial hyperresponsiveness [226,227] and wheezing may also be prevalent in subjects with recent hypersensitivity pneumonitis, especially in dairy farmers [228,229].…”
Section: Environmental or Occupational Exposurementioning
confidence: 99%
“…Nonspecific bronchial hyperresponsiveness [226,227] and wheezing may also be prevalent in subjects with recent hypersensitivity pneumonitis, especially in dairy farmers [228,229].…”
Section: Environmental or Occupational Exposurementioning
confidence: 99%
“…In our study, special reimbursement rights for the cost of asthma medication occurred in 8.6% of patients with farmer's lung during an average of 7.8 years of follow-up. Kokkarinen et al [10] found such reimbursement rights in 7.2% during a follow-up of 5 years, but did not include cases of occupational asthma. Erkinjuntti-Pekkanen found asthma diagnosed by physician in 16% of farmer's-lung patients during a mean follow-up of 14 years [5].…”
Section: Discussionmentioning
confidence: 95%
“…The incidence of asthma was increased especially during the first years after diagnosis of farmer's lung. In a previous Finnish register follow-up of patients diagnosed with farmer's lung in 1983-1988, most of the cases of asthma occurred during the first 3 years of the follow-up [10]. No comparison was made with farmers in general in that study, and cases of recognized occupational asthma were not included.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Les manifestations cliniques d'hyperréactivité bronchique (asthme, sibilances) ont été rapportées de façon accrue chez les sujets porteurs de pneumopathie d'hypersensibilité dans l'évolution de leur maladie, notamment en zone de production laitière [25,26]. En outre, plusieurs études suggèrent fortement un excès d'hyperréactivité bronchique chimique chez les patients atteints de pneumopathie d'hypersensibilité [27][28][29].…”
Section: Hyperréactivité Bronchiqueunclassified